Flux flow in current driven mesoscopic superconductors: size effects - Sanchez Lotero, Pedro Nel (2016)
Flux-flow phenomena in a superconducting mesoscopic stripe submitted to an appliedcurrent and external magnetic field is studied. The time-dependent Ginzburg-Landauequations are solved numerically to obtain the electric and magnetic response of thesystem. It is shown that the I-V curves, for the wider strips, present a universalbehaviour. The dependence of the flux-flow resistivity on the magnetic field and widthallow us to propose a criterion characterizing, both, the macroscopic and mesoscopicregimes. The power spectrum of the average voltage permits identifying the effect ofsurface currents in vortices movement. Based on the maximum value of the power spectrumfirst harmonic we propose a geometric condition for matching between the sample dimensionsand the vortex lattice parameter.